Tapping: Political Delict That Injure The Rule of Law in The Modern States (Case of Indonesia President Susilo Bambang Yudhoyono/SBY Tapping by Australian Signal Directorate/ASD) - Noor Fatimah Mediawati (Rechtsidee, 2014)
The interception case of SBY, his wife and the other official, by ASD/ Australian Signal Directorate to be a central topic in this paper. Start of the case, and then it searches in the category, such as general criminal offense, special criminal offense, or political criminal offense. The study becomes interesting because the tapper country and his object country have the same characteristic, that is the country with supremacy of law. With the result that, the criminal offense, specifically for this interception, it is like injury to the rule of law. How To Cite: Mediawati, N. (2014). Tapping: Political Delict That Injure The Rule of Law in The Modern States (Case of Indonesia President Susilo Bambang Yudhoyono/SBY Tapping by Australian Signal Directorate/ASD). Rechtsidee, 1(2), 163-174. doi:http://dx.doi.org/10.21070/jihr.v1i2.104